Pharmacokinetics of Acetaminophen and Metformin Hydrochloride in Rats After Exposure to Simulated High Altitude Hypoxia - Zhu, Jun-bo; Yang, Jian-xin; Nian, Yong-qiong; Liu, Gui-qin; Duan, Ya-bin; Bai, Xue; Wang, Qian; Zhou, Yang; Wang, Xue-jun; Qu, Ning; Li, Xiang-yang (Frontiers in Pharmacology, 2021)
The pharmacokinetic characteristics of drugs were altered under high altitude hypoxia, thereby affecting the absorption, distribution, metabolism, and excretion of drug. However, there are few literatures on the pharmacokinetic changes of antipyretic and pain-relieving drugs and cardiovascular system drugs at high altitude. This study aimed to evaluate the pharmacokinetics of acetaminophen and metformin hydrochloride in rats under simulated high altitude hypoxia condition. Mechanically, the protein and mRNA expression of uridine diphosphate glucuronyltransferase 1A1 (UGT1A1) and organic cation transporter 2 (OCT2) were investigated by enzyme linked immunosorbent assay (ELISA) and quantitative real-time polymerase chain reaction (qRT-PCR), respectively. Compared with the normoxia group, the t1/2 and AUC of acetaminophen were significantly increased, and the CL/F was significantly decreased in rats after exposure to simulated high altitude hypoxia. The t1/2 of metformin hydrochloride was significantly increased by simulated high altitude hypoxia. No significant differences in AUC and CL/F of metformin hydrochloride were observed when comparing the hypoxia group with the normoxia group. The protein and mRNA expression of UGT1A1 and OCT2 were decreased significantly under hypoxia in rats. This study found obvious changes in the pharmacokinetics of acetaminophen and metformin hydrochloride in rats after exposure to simulated high altitude hypoxia, and they might be due to significant decreases in the expressions of UGT1A1 and OCT2. To sum up, our data suggested that the pharmacokinetics of acetaminophen and metformin hydrochloride should be reexamined, and the optimal dose should be reassessed under hypoxia exposure.